Mathematical Modeling of Static Data Attribute Encryption Based on Big Data Technology - Yutang Liu; Qin Zhang (Journal of Function Spaces)
Attribute encryption is an effective one to many network communication technologies, which supports flexible access control strategies and is very suitable for fine-grained access control in large-scale information systems. In order to improve the attributes of static data, encryption technology can provide a reliable technical guarantee for network security. This paper presents a mathematical modeling method of static data attribute encryption based on big data technology. The big data redundancy elimination algorithm based on similarity calculation is analyzed. By using static data attribute encryption based on big data technology, the length of encrypted data packets will not increase, and partial redundancy of fragments can be eliminated, which can greatly improve the efficiency of the system. The attribute-based encryption mechanism uses attributes as public keys, and the decryption user is a group; so, the encryption efficiency is very high. It can realize efficient encryption and decryption, as well as flexible access control based on user attributes. This scheme can reflect the importance of attributes; so, it is more practical.